Cytochemical Localization of Polysaccharides in Dendrobium officinale and the Involvement of DoCSLA6 in the Synthesis of Mannan Polysaccharides - He, Chunmei; Wu, Kunlin; Zhang, Jianxia; Liu, Xuncheng; Zeng, Songjun; Yu, Zhenming; Zhang, Xinghua; Teixeira da Silva, Jaime A.; Deng, Rufang; Tan, Jianwen; Luo, Jianping; Duan, Jun (Frontiers in Plant Science, 2017)
Dendrobium officinale is a precious traditional Chinese medicinal plant because of its abundant polysaccharides found in stems. We determined the composition of water-soluble polysaccharides and starch content in D. officinale stems. The extracted water-soluble polysaccharide content was as high as 35% (w/w). Analysis of the composition of monosaccharides showed that the water-soluble polysaccharides were dominated by mannose, to a lesser extent glucose, and a small amount of galactose, in a molar ratio of 223:48:1. Although starch was also found, its content was less than 10%. This result indicated that the major polysaccharides in D. officinale stems were non-starch polysaccharides, which might be mannan polysaccharides. The polysaccharides formed granules and were stored in plastids similar to starch grains, were localized in D. officinale stems by semi-thin and ultrathin sections. CELLULOSE SYNTHASE-LIKE A (CSLA) family members encode mannan synthases that catalyze the formation of mannan polysaccharides. To determine whether the CSLA gene from D. officinale was responsible for the synthesis of mannan polysaccharides, 35S:DoCSLA6 transgenic lines were generated and characterized. Our results suggest that the CSLA family genes from D. officinale play an important role in the biosynthesis of mannan polysaccharides.